(untitled) (Journal of the College of Basic Education, 2022)
What makes Iraq and its heritage increasingly important is that it is one of the oldest civilized centers in human history. Its land witnessed the oldest human experiences and attempts in various kinds of knowledge, science, ideas and literature. Iraqi activities throughout the ages, despite the multiplicity of forms of buildings and their different functions, but the house stood out among them in terms of antiquity and abundance, just as the foundations of its planning, architecture and building materials were the basis on which other forms of public buildings such as temples and towers imposed by religious rituals were built.